2015
DOI: 10.2196/jmir.5043
|View full text |Cite
|
Sign up to set email alerts
|

Apps and Adolescents: A Systematic Review of Adolescents’ Use of Mobile Phone and Tablet Apps That Support Personal Management of Their Chronic or Long-Term Physical Conditions

Abstract: BackgroundThe prevalence of physical chronic or long-term conditions in adolescents aged 10-24 years is rising. Mobile phone and tablet mobile technologies featuring software program apps are widely used by these adolescents and their healthy peers for social networking or gaming. Apps are also used in health care to support personal condition management and they have considerable potential in this context. There is a growing body of literature on app use in health contexts, thereby making a systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
225
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(243 citation statements)
references
References 58 publications
14
225
0
4
Order By: Relevance
“…Personal management of chronic physical conditions requires 5 main skills: problem solving, decision-making, resource utilization, patient-doctor relationships, and taking action. [42] The prototype mobile application can assist in aiding problem solving and decision making by providing disease-specific and lifestyle information, as well as create portable tools that adolescents can use to convey important disease information, including a portable medical summary and a CHD diagram of their disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Personal management of chronic physical conditions requires 5 main skills: problem solving, decision-making, resource utilization, patient-doctor relationships, and taking action. [42] The prototype mobile application can assist in aiding problem solving and decision making by providing disease-specific and lifestyle information, as well as create portable tools that adolescents can use to convey important disease information, including a portable medical summary and a CHD diagram of their disease.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of adolescents' use of mobile applications that support management of chronic disease from 2015 revealed that the available four mobile apps that assisted youth with chronic disease that contained pre/post or randomized control data. [42] Two of these apps were focused on diabetes type 1, and the other two focused on asthma and cancer. Three out of the four studies reported some level of patient involvement in the design, development and/or evaluation of the app This study noted that the dearth of studies and overall small sample size emphasized the need for future studies on the development, use, and effectiveness of mobile apps to support adolescent personal management of their chronic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sustained mobile data collection is challenging due to lack of engagement and adherence [23,24]. Indeed, adherence is generally low for mHealth data collection apps [25], which is also true for substance use apps.…”
mentioning
confidence: 99%
“…For example, a recent review of mHealth apps for substance use (including text messaging and apps) concluded that engagement is a critical limitation, with most use declining quickly over brief periods of time (2 weeks to 3 months) [26]; importantly, few studies included adolescents or emerging adults [27]. Similarly, research on behavioral health apps is also limited among youth, with engagement challenging, potentially because youth may habituate to apps [24] as well as competing demands due to frequent use of other apps (e.g., social media [22] or entertainment apps [28]). …”
mentioning
confidence: 99%